2021
DOI: 10.1021/acs.jmedchem.1c00935
|View full text |Cite
|
Sign up to set email alerts
|

JNJ-67569762, A 2-Aminotetrahydropyridine-Based Selective BACE1 Inhibitor Targeting the S3 Pocket: From Discovery to Clinical Candidate

Abstract: The discovery of a novel 2-aminotetrahydropyridine class of BACE1 inhibitors is described. Their pKa and lipophilicity were modulated by a pending sulfonyl group, while good permeability and brain penetration were achieved via intramolecular hydrogen bonding. BACE1 selectivity over BACE2 was achieved in the S3 pocket by a novel bicyclic ring system. An optimization addressing reactive metabolite formation, cardiovascular safety, and CNS toxicity is described, leading to the clinical candidate JNJ-67569762 (12)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Several small molecules targeting BACE1 have been tested in the clinical trials for the treatment of AD. 45 , 46 , 47 In this study, we found that compound D reduced BACE1 expression levels in a dose‐dependent manner, thereby downregulating Aβ levels. However, compound D had no significant effect on the expression of PS1, a member of the γ‐secretase family of AD‐related genes.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Several small molecules targeting BACE1 have been tested in the clinical trials for the treatment of AD. 45 , 46 , 47 In this study, we found that compound D reduced BACE1 expression levels in a dose‐dependent manner, thereby downregulating Aβ levels. However, compound D had no significant effect on the expression of PS1, a member of the γ‐secretase family of AD‐related genes.…”
Section: Discussionmentioning
confidence: 52%
“…Many previous reports have indicated that BACE1 is a target for the treatment of AD. Several small molecules targeting BACE1 have been tested in the clinical trials for the treatment of AD 45–47 . In this study, we found that compound D reduced BACE1 expression levels in a dose‐dependent manner, thereby downregulating Aβ levels.…”
Section: Discussionmentioning
confidence: 62%
“…73 Chromatography Hydrophobicity Index (CHI). 74 Cassettes containing aliquots of 1 mM compound in DMSO stock solutions to be tested were prepared. An aliquot of a DMSO solution containing a set of 10 calibration compounds with known CHI pH values was added to each cassette to achieve the desired test compound analysis concentration (typically 50 nM).…”
Section: ((2r3s)-2-((benzyloxy)methyl)tetrahydrofuran-3-yl)methanol (...mentioning
confidence: 99%
“…Janssen Pharmaceutica carried out the synthesis of several compounds that can be useful for the treatment or prevention of diseases such as cancer. [57] Some of these novel compounds which can serve as myeloid cell leukemia-1 (MCL-1) inhibitors have been synthesized utilizing a Julia-Kocienski olefination approach for the construction of the trisubstituted double bond present in their structure. More specifically, α-fluoro-BT-sulfone 102 reacted with aldehyde 103 in the presence of tBuOK at À 21 °C in THF to afford an E,Z-mixture of fluoro-olefins 104 (Scheme 19).…”
Section: Synthesis Of Analogs Of Natural Products and Compounds With ...mentioning
confidence: 99%